PENERAPAN TEKNOLOGI DAN INOVASI UNTUK PEMBANGUNAN BERKELANJUTAN DI DESA SUKAHATI KECAMATAN CILAWU KABUPATEN GARUT - Sutedi, Ade (Institut Teknologi Garut, 2024)
Community empowerment is an activity to increase community participation in fulfilling life needs and solving problems experienced by the community. This is implemented through the Real Work Lecture (KKN) program which is a community service-based activity to increase the concern of the academic community of higher education institutions for the conditions of the community and their environment. The 2024 Garut Institute of Technology Thematic KKN was implemented in Cilawu District, Garut Regency using the methods of counseling, demonstrations, and mentoring community groups. The results showed a positive response from the village and high active participation of the community, including participating in health programs, namely healthy gymnastics, stunting counseling through integrated health posts, which are estimated to have almost 30% of the community participating in the activities. In addition, several outputs from the application of technology and innovation produced: (1) Increasing the competitiveness of MSMEs in the community in the form of knowledge of product packaging using modern designs, tools and plastic press bags and Internet Marketing marketing techniques; (2) Increasing knowledge about ICT for Junior High School (SMP) students; (3) Improving road access for the community to carry out daily activities. In addition, there is an increase in discipline and a positive response from the community towards KKN activities by looking at the output of the products produced.